2011
DOI: 10.1007/s13105-011-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet based on dried bovine brain: an effective animal model of dyslipidemia and insulin resistance

Abstract: Currently, there are no reports in the literature demonstrating any animal model that ingests one of the fattiest animal food source, the bovine brain. We hypothesized that a high-fat diet (HFD), based on dried bovine brain, could be used to develop an animal model possessing a spectrum of insulin resistance-related features. The HFD was formulated with 40% dried bovine brain plus 16.4% butter fat, prepared in-house. Furthermore, the diet contained 52% calories as fat and 73% of total fatty acids were saturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
(48 reference statements)
1
5
0
3
Order By: Relevance
“…Few small-sized cavities were found, whereas in the HFD group many small-sized cavities were found ( Figure 1H ). These results indicated that HFD impaired the homeostasis of glucose and lipids, which is in agreement with previous studies (Araujo et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…Few small-sized cavities were found, whereas in the HFD group many small-sized cavities were found ( Figure 1H ). These results indicated that HFD impaired the homeostasis of glucose and lipids, which is in agreement with previous studies (Araujo et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…Laboratory Commercial rodent chow (Labina ® , Purina) was used as a control diet (57.3% carbohydrate, 41.2% cornstarch), as this diet has been used in previous studies as a control diet 51 52 .…”
Section: Methodsmentioning
confidence: 99%
“…Although considering the protective effects of a high-fat diet in short-term, the increased fat-intake will become habitual [ 36 , 37 ] and thus will lead to a deterioration of the cardiometabolic situation in long-term [ 38 , 39 ]. The after-effects of a long-lasting high-fat diet were shown in rodents and include increasing levels of insulin, insulin resistance and mild hyperglycemia [ 24 , 32 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%